Fluorapatite nanorod with magnesium-rich amorphous layer on the surface and preparation method thereof

The method of preparing fluoroapatite nanorods with a magnesium-rich amorphous layer addresses the lack of such coatings, achieving effective and scalable production of nanorods with enhanced mechanical properties.

CN117246991BActive Publication Date: 2024-12-24CHINA HUBEI LONGZHONG LABORATORY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311134715.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2024-12-24
Estimated Expiration
2043-09-04

AI Technical Summary

Technical Problem

There is no report on hydroxyapatite or fluoroapatite with a surface coated with a magnesium-rich amorphous layer to replicate the excellent mechanical properties of tooth enamel.

Method used

A method for preparing fluoroapatite nanorods with a surface-coated magnesium-rich amorphous layer by dissolving calcium and magnesium salts in water, adding a phosphate and fluoride solution, controlling the dropping rate and aging, followed by centrifugation and freeze-drying to form nanorods with a specific ion concentration and morphology.

Benefits of technology

Regulates crystallinity and morphology, enabling large-scale production of fluoroapatite nanorods with a magnesium-rich amorphous layer, maintaining mechanical properties similar to tooth enamel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117246991B_ABST
    Figure CN117246991B_ABST
Patent Text Reader

Abstract

The invention discloses a fluoroapatite nanorod with a magnesium-rich amorphous layer on the surface and a preparation method thereof. The preparation method of the fluoroapatite nanorod with a magnesium-rich amorphous layer on the surface comprises the following steps: dissolving a soluble calcium salt and a soluble magnesium salt in water to obtain a mixed solution A; dissolving a soluble phosphate and a soluble fluoride salt in water to obtain a mixed solution B; slowly dropping the mixed solution B into the mixed solution A, and after the dropping process is completed, sequentially standing and aging at room temperature, centrifugal washing, and freeze drying are performed to obtain a fluoroapatite nanorod powder with a magnesium-rich amorphous layer on the surface; the invention regulates the crystallinity and morphology of the fluoroapatite nanorod by changing the concentration of magnesium ions in the mixed solution A and the dropping rate of the mixed solution B, and successfully realizes the large-scale preparation of the fluoroapatite nanorod powder with a magnesium-rich amorphous layer on the surface through a one-step method; the preparation process of the invention has simple raw materials, low cost, mild reaction, and simple operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of bionic mineralized nano materials, and particularly relates to a fluorapatite nanorod with a surface coated with a magnesium-rich amorphous layer and a preparation method thereof. Background Art

[0002] Highly mineralized biomaterials such as shell nacre and tooth enamel can achieve excellent comprehensive mechanical properties by combining simple inorganic minerals with organic matter. For example, shell nacre is composed of 95wt% calcium carbonate aragonite phase nanosheets and 5wt% chitin, and its fracture toughness is more than 3,000 times that of natural aragonite minerals, while maintaining high strength. Tooth enamel is the hardest tissue in the human body and is precisely assembled from hydroxyapatite nanorods. This multi-level ordered structure composed of nanorods gives tooth enamel good mechanical strength and excellent viscoelastic properties. Previous research results have shown that the complex and ingenious multi-level microstructure formed by the directional assembly of nano-units can produce stable sliding of nano-units, which can achieve excellent fracture toughness without sacrificing strength.

[0003] With the in-depth study of tooth enamel, in addition to the characteristic of multi-level microstructure, researchers have found that tooth enamel has another common feature, that is, the presence of inorganic amorphous phases enriched with trace elements such as magnesium and iron. These amorphous phases usually surround the surface of apatite nanorod crystals, occupy the space between nanocrystal blocks, and form amorphous interstitial phases. The amorphous phase has abundant unsaturated bonds, which can form a strong chemical connection with nanocrystals, provide better adhesion, and play a role in interface enhancement.

[0004] In order to replicate the excellent mechanical properties of tooth enamel, it is necessary to synthesize similar nanorod assembly units with an amorphous layer rich in trace elements such as magnesium and iron on the surface. At present, there is no report on hydroxyapatite or fluoroapatite with an amorphous layer rich in magnesium on the surface. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, propose a fluoroapatite nanorod with a surface coated with a magnesium-rich amorphous layer and a preparation method thereof, and solve the technical problem that the related work of hydroxyapatite or fluoroapatite with a surface coated with a magnesium-rich amorphous layer in the prior art has not been reported.

[0006] In a first aspect, the present invention provides a method for preparing a fluoroapatite nanorod having a surface coated with a magnesium-rich amorphous layer, comprising the following steps:

[0007] Dissolving a soluble calcium salt and a soluble magnesium salt in water to obtain a mixed solution A;

[0008] Dissolving a soluble phosphate and a soluble fluoride salt in water to obtain a mixed solution B;

[0009] The mixed solution B is slowly added dropwise to the mixed solution A. After the addition process is completed, the mixed solution is allowed to stand for aging at room temperature, centrifuged for washing, and freeze-dried to obtain a fluoroapatite nanorod powder with a surface coated with a magnesium-rich amorphous layer. In the mixed solution A, the concentration of calcium ions is 5.4-10.8 mM, and the concentration of magnesium ions is 1.2-1.8 mM. In the mixed solution B, the concentration of phosphate ions is 3.24-6.48 mM, and the concentration of fluoride ions is 1.08-2.16 mM. The dropping rate of the mixed solution B is 3.57-5 ml / h.

[0010] In a second aspect, the present invention provides a fluoroapatite nanorod with a surface coated with a magnesium-rich amorphous layer, wherein the fluoroapatite nanorod with a surface coated with a magnesium-rich amorphous layer is obtained by the preparation method of the fluoroapatite nanorod with a surface coated with a magnesium-rich amorphous layer provided in the first aspect of the present invention.

[0011] Compared with the prior art, the beneficial effects of the present invention include:

[0012] The present invention regulates the crystallinity and morphology of fluorapatite nanorods by changing the concentration of magnesium ions in a mixed solution A and the dropping rate of a mixed solution B, and successfully realizes large-scale preparation of fluorapatite nanorod powders with a surface-coated magnesium-rich amorphous layer through a one-step method; the preparation process of the present invention has simple raw materials, low cost, mild reaction and simple operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 These are transmission electron microscope low-magnification and high-magnification photographs of the fluorapatite nanorods with a surface coated with a magnesium-rich amorphous layer prepared in Example 1 of the present invention;

[0014] Figure 2 The electron scanning photo and transmission electron micrograph of the fluorapatite nanospheres prepared under the condition of changing the drop acceleration rate of the mixed solution B in Comparative Example 1 of the present invention;

[0015] Figure 3 These are transmission electron microscope low-magnification and high-magnification photographs of amorphous fluoroapatite nanorods prepared under the condition of changing the magnesium ion concentration in Comparative Example 2 of the present invention;

[0016] Figure 4 These are transmission electron microscope low-magnification and high-magnification photographs of completely crystallized fluoroapatite nanorods prepared under the condition of changing the magnesium ion concentration in Comparative Example 3 of the present invention;

[0017] Figure 5 This is an electron scanning photograph of the fluorapatite nanospheres prepared under the conditions of changing the magnesium ion concentration and the drop acceleration rate of the mixed solution B in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0019] In a first aspect, the present invention provides a method for preparing a fluoroapatite nanorod having a surface coated with a magnesium-rich amorphous layer, comprising the following steps:

[0020] S1. Dissolving a soluble calcium salt and a soluble magnesium salt in water to obtain a mixed solution A; wherein, in the mixed solution A, the concentration of calcium ions is 5.4-10.8 mM, further 6.5-7 mM, further 6.8 mM, and the concentration of magnesium ions is 1.2-1.8 mM, further 1.4-1.6 mM, further 1.5 mM.

[0021] S2. Dissolve soluble phosphate and soluble fluoride salt in water to obtain a mixed solution B; wherein, in the mixed solution B, the concentration of phosphate ions is 3.24-6.48 mM, further 3.8-4.3 mM, further 4.08 mM, and the concentration of fluoride ions is 1.08-2.16 mM, further 1.2-1.5 mM, further 1.36 mM.

[0022] S3. Slowly drop the mixed solution B into the mixed solution A. After the dropping process is completed, the mixed solution is allowed to stand at room temperature for aging, centrifuged and washed, and freeze-dried to obtain a fluoroapatite nanorod powder with a surface coated with a magnesium-rich amorphous layer; wherein the dropping rate of the mixed solution B is 3.57-5 ml / h, further 4-4.5 ml / h, and further 4.16 ml / h.

[0023] In the present invention, the formation mechanism of the fluoroapatite nanorods with a surface-coated magnesium-rich amorphous layer is a growth mode based on nanoparticle aggregation, more specifically, the random attachment of nanoparticles. When mixed solution B is slowly added dropwise to mixed solution A, many magnesium-containing fluoroapatite amorphous nanoclusters are formed. As the dropping process proceeds, the number of nanoclusters increases, and random attachment and oriented crystallization occur. In this process, magnesium ions are squeezed to the edge of the nanorods to form fluoroapatite nanorods with a surface-coated magnesium-rich amorphous layer. In this process, the preparation of the fluoroapatite nanorods with a surface-coated magnesium-rich amorphous layer is closely related to the magnesium ion concentration in the mixed solution A and the dropping rate of the mixed solution B. The dropping rate is controlled at 3.57-5ml / h and the magnesium ion concentration is controlled at 1.2-1.8mM to obtain the fluoroapatite nanorods with a surface-coated magnesium-rich amorphous layer. If the magnesium ion concentration exceeds this range, even if the dropping rate is low, only amorphous fluoroapatite nanospheres can be obtained.

[0024] In this embodiment, the soluble calcium salt is calcium chloride, the soluble magnesium salt is magnesium chloride, the soluble phosphate is at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate, and sodium phosphate, and the soluble fluoride salt is sodium fluoride. Those skilled in the art should understand that the above calcium salt, magnesium salt, phosphate and fluoride salt all include their hydrate forms.

[0025] In this embodiment, in the mixed solution A and the mixed solution B, Ca 2+ : F - :PO4 3- The molar ratio is (4-6):1:(2-4), and further is 5:1:3.

[0026] In this embodiment, the volume ratio of the mixed solution A to the mixed solution B is 1:(0.8-1.2), further 1:1.

[0027] In some specific embodiments of the present invention, the volume of the mixed solution A is 50-100 ml.

[0028] In some embodiments of the present invention, the dripping rate of the mixed solution B is strictly controlled by a peristaltic pump.

[0029] In this embodiment, the room temperature aging time is 6-24 hours, further 12 hours.

[0030] In this embodiment, the freeze-drying time is 12-24 hours.

[0031] In a second aspect, the present invention provides a fluoroapatite nanorod with a surface coated with a magnesium-rich amorphous layer, wherein the fluoroapatite nanorod with a surface coated with a magnesium-rich amorphous layer is obtained by the preparation method of the fluoroapatite nanorod with a surface coated with a magnesium-rich amorphous layer provided in the first aspect of the present invention.

[0032] In some specific embodiments of the present invention, the diameter of the fluorapatite nanorods coated with a magnesium-rich amorphous layer is 60-80nm, the length is 100-300nm, the interior of the nanorods is well-crystallized fluorapatite crystals, and the surface of the nanorods is a 3-10nm thick fluorapatite amorphous layer formed by the aggregation of magnesium ions.

[0033] Example 1

[0034] This embodiment provides a method for preparing a fluoroapatite nanorod with a magnesium-rich amorphous layer on its surface, comprising the following steps:

[0035] In the first step, 50 ml of a mixed solution A containing 6.8 mM calcium chloride and 1.5 mM magnesium chloride was prepared at room temperature and stirred until fully dissolved.

[0036] In the second step, 50 ml of a mixed solution B containing 4.08 mM disodium hydrogen phosphate dodecahydrate and 1.36 mM sodium fluoride was prepared at room temperature and stirred until fully dissolved.

[0037] In the third step, the mixed solution B is slowly added to the mixed solution A with the help of a peristaltic pump. As the reaction proceeds, white precipitate is continuously produced. The dripping rate of the peristaltic pump is 4.16 ml / h.

[0038] The fourth step is to allow the white suspension obtained after the third step of titration to stand at room temperature for 12 hours.

[0039] In the fifth step, the white suspension in the fourth step is centrifuged and washed, and then transferred to a freeze dryer and dried for 12 hours to obtain fluoroapatite nanorods with a length of 100-300 nm and a diameter of 60-80 nm and a surface coated with a magnesium-rich amorphous layer ( Figure 1 ).

[0040] Comparative Example 1

[0041] In the first step, 50 ml of a mixed solution A containing 6.8 mM calcium chloride and 1.5 mM magnesium chloride was prepared at room temperature and stirred until fully dissolved.

[0042] In the second step, 50 ml of a mixed solution B containing 4.08 mM disodium hydrogen phosphate dodecahydrate and 1.36 mM sodium fluoride was prepared at room temperature and stirred until fully dissolved.

[0043] In the third step, the mixed solution B is slowly added to the mixed solution A with the help of a peristaltic pump. As the reaction proceeds, white precipitate is continuously produced. The dripping rate of the peristaltic pump is 8.32 ml / h.

[0044] The fourth step is to allow the white suspension obtained after the third step of titration to stand at room temperature for 12 hours.

[0045] In the fifth step, the white suspension in the fourth step is centrifuged and washed, and then transferred to a freeze dryer and dried for 12 hours to obtain amorphous fluoroapatite nanospheres with a diameter of about 150 nm ( Figure 2 ).

[0046] By comparing the results of comparative example 1 with those of embodiment 1, it can be seen that when the dropping rate is too high, only amorphous fluoroapatite nanospheres can be prepared, indicating that the selection of the dropping rate has a great influence on the preparation of fluoroapatite nanorods coated with a magnesium-rich amorphous layer on the surface.

[0047] Comparative Example 2

[0048] In the first step, 50 ml of a mixed solution A containing 6.8 mM calcium chloride and 3.25 mM magnesium chloride was prepared at room temperature and stirred until fully dissolved.

[0049] In the second step, 50 ml of a mixed solution B containing 4.08 mM disodium hydrogen phosphate dodecahydrate and 1.36 mM sodium fluoride was prepared at room temperature and stirred until fully dissolved.

[0050] In the third step, the mixed solution B is slowly added to the mixed solution A with the help of a peristaltic pump. As the reaction proceeds, white precipitate is continuously produced. The dripping rate of the peristaltic pump is 4.16 ml / h.

[0051] The fourth step is to allow the white suspension obtained after the third step of titration to stand at room temperature for 12 hours.

[0052] In the fifth step, the white suspension in the fourth step is centrifuged and washed, and then transferred to a freeze dryer and dried for 12 hours to obtain amorphous fluoroapatite nanorods with a length of 200-300 nm and a diameter of 40-50 nm ( Figure 3 ).

[0053] By comparing the results of Comparative Example 2 with those of Example 1, it can be seen that increasing the magnesium ion concentration in the mixed solution A can only produce amorphous fluoroapatite nanorods, indicating that too high a magnesium ion concentration will significantly reduce the crystallinity of fluoroapatite nanorods.

[0054] Comparative Example 3

[0055] In the first step, 50 ml of a mixed solution A with a concentration of 6.8 mM calcium chloride and 0 mM magnesium chloride was prepared at room temperature and stirred until fully dissolved.

[0056] In the second step, 50 ml of a mixed solution B containing 4.08 mM disodium hydrogen phosphate dodecahydrate and 1.36 mM sodium fluoride was prepared at room temperature and stirred until fully dissolved.

[0057] In the third step, the mixed solution B is slowly added to the mixed solution A with the help of a peristaltic pump. As the reaction proceeds, white precipitate is continuously produced. The dripping rate of the peristaltic pump is 4.16 ml / h.

[0058] The fourth step is to allow the white suspension obtained after the third step of titration to stand at room temperature for 12 hours.

[0059] In the fifth step, the white suspension in the fourth step is centrifuged and washed, and then transferred to a freeze dryer and dried for 12 hours to obtain completely crystallized fluoroapatite nanorods with a length of 200-300 nm and a diameter of 80-100 nm ( Figure 4 ).

[0060] By comparing the results of Comparative Example 3 with those of Example 1, it can be seen that only completely crystalline fluoroapatite nanorods can be prepared without adding magnesium ions into the mixed solution A.

[0061] Comparative Example 4

[0062] In the first step, 50 ml of a mixed solution A containing 6.8 mM calcium chloride and 3.25 mM magnesium chloride was prepared at room temperature and stirred until fully dissolved.

[0063] In the second step, 50 ml of a mixed solution B containing 4.08 mM disodium hydrogen phosphate dodecahydrate and 1.36 mM sodium fluoride was prepared at room temperature and stirred until fully dissolved.

[0064] In the third step, the mixed solution B is slowly added to the mixed solution A with the help of a peristaltic pump. As the reaction proceeds, white precipitate is continuously produced. The dripping rate of the peristaltic pump is 0.56 ml / h.

[0065] The fourth step is to allow the white suspension obtained after the third step of titration to stand at room temperature for 12 hours.

[0066] In the fifth step, the white suspension in the fourth step is centrifuged and washed, and then transferred to a freeze dryer and dried for 12 hours to obtain amorphous fluoroapatite nanospheres with a diameter of 80-100 nm ( Figure 5 ).

[0067] By comparing the results of Comparative Example 4 with those of Example 1, it can be seen that if the magnesium ion concentration in the mixed solution A is too high, only amorphous fluoroapatite nanospheres can be obtained even if the dropping rate is further reduced, indicating that the present invention can achieve large-scale preparation of fluoroapatite nanorod powders with a magnesium-rich amorphous layer on the surface only by selecting an appropriate magnesium ion concentration and a dropping rate.

[0068] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a fluoroapatite nanorod with a magnesium-rich amorphous layer on its surface, characterized in that: The following steps are involved: Dissolving a soluble calcium salt and a soluble magnesium salt in water to obtain a mixed solution A; Dissolving a soluble phosphate and a soluble fluoride salt in water to obtain a mixed solution B; The mixed solution B is slowly added dropwise to the mixed solution A, and after the addition process is completed, the solution is allowed to stand at room temperature for aging, centrifuged for washing, and freeze-dried to obtain a fluoroapatite nanorod powder with a magnesium-rich amorphous layer on the surface; wherein, In the mixed solution A, the concentration of calcium ions is 6.5-7 mM, and the concentration of magnesium ions is 1.4-1.6 mM; in the mixed solution B, the concentration of phosphate ions is 3.8-4.3 mM, and the concentration of fluoride ions is 1.2-1.5 mM; the dripping rate of the mixed solution B is 4-4.5 ml / h.

2. The method for preparing the fluoroapatite nanorods having a surface coated with a magnesium-rich amorphous layer according to claim 1, characterized in that: In the mixed solution A and the mixed solution B, Ca 2+ : F - :PO4 3- The molar ratio is (4~6):1:(2~4).

3. The method for preparing the fluoroapatite nanorods with a surface coated with a magnesium-rich amorphous layer according to claim 1, characterized in that: The volume ratio of the mixed solution A to the mixed solution B is 1:(0.8-1.2).

4. The method for preparing the fluoroapatite nanorods with the surface coated with a magnesium-rich amorphous layer according to claim 1, characterized in that: The volume of the mixed solution A is 50-100 ml.

5. The method for preparing the fluoroapatite nanorods with the surface coated with a magnesium-rich amorphous layer according to claim 1, characterized in that: The soluble calcium salt is calcium chloride, the soluble magnesium salt is magnesium chloride, the soluble phosphate is at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium phosphate, and the soluble fluoride salt is sodium fluoride.

6. The method for preparing the fluoroapatite nanorods with the surface coated with a magnesium-rich amorphous layer according to claim 1, characterized in that: The room temperature standing aging time is 6-24h.

7. The method for preparing the fluoroapatite nanorods with the surface coated with a magnesium-rich amorphous layer according to claim 1, characterized in that: The freeze-drying time is 12-24 h.

8. A fluoroapatite nanorod with a magnesium-rich amorphous layer on its surface, characterized in that: The fluoroapatite nanorods with a surface coated with a magnesium-rich amorphous layer are obtained by the preparation method of the fluoroapatite nanorods with a surface coated with a magnesium-rich amorphous layer according to any one of claims 1 to 7.

9. The fluoroapatite nanorods with a surface coated with a magnesium-rich amorphous layer according to claim 8, characterized in that: The diameter of the fluorapatite nanorods coated with a magnesium-rich amorphous layer is 60-80 nm, the length is 100-300 nm, the interior of the nanorods is well-crystallized fluorapatite crystals, and the surface of the nanorods is a 3-10 nm thick fluorapatite amorphous layer formed by the aggregation of magnesium ions.

Citation Information

Patent Citations

  • Preparation method of fibroin-compounded fluorapatite whisker-reinforced biological ceramics

    CN103183506A

  • Dental composite resin containing dumbbell-shaped fluorapatite filler and preparation method thereof

    CN112790993A

  • Fluoroapatite quasi-equiaxed nanocrystal and preparation method thereof

    CN114804059A

  • Making method of fluor apatite

    CN1475436A

  • A method for producing fluorapatite crystals

    WO2022162091A1